Acute His‐Bundle Injury Current during Permanent His‐Bundle Pacing Predicts Excellent Pacing Outcomes. Issue 5 (14th January 2015) - VIJAYARAMAN, PUGAZHENDHI; DANDAMUDI, GOPI; WORSNICK, SARAH; ELLENBOGEN, KENNETH A.
<x xml:space="preserve">Abstract</x> Introduction His‐bundle (HB) pacing (P) is a physiological alternative to right ventricular pacing (RVP), but is technically challenging and limited by higher pacing thresholds. Myocardial injury current (IC) recorded during right ventricular lead placement implies good tissue contact and is associated with low‐pacing thresholds. IC at the HB has not been previously described. We hypothesized that HBIC during permanent HBP may be associated with lower pacing thresholds. Methods Permanent HBP was performed using Medtronic Select Securetm (Medtronic Inc., Minneapolis, MN, USA) delivered via a fixed‐curve (C315 His) sheath. HB electrogram (EGM) was recorded in a unipolar fashion from the lead tip. Presence or absence of HBIC was documented. HBP threshold, sensing, and impedances were recorded at implant, 2 weeks, 2 months, and 1 year. Results Sixty patients (age 72 ± 15 years; male 55%, sick sinus syndrome 40%, atrioventricular block 60%, fluoroscopy duration 9.2 ± 3.7 minutes) underwent successful permanent HBP. HBIC was recorded in 22 (37%) patients (group I). HBEGM without IC was recorded in the remaining 38 (63%) patients (group II). Pacing threshold at implant, 2 weeks, 2 months, and 1 year were significantly lower in group I (1.16 ± 0.4 V; 1.18 ± 0.5 V; 1.23 ± 0.6 V; 1.3 ± 0.6 V @ 0.5 ms) compared to group II (1.75 ± 0.7 V; 1.82 ± 0.8 V; 1.93 ± 0.8 V; 1.98 ± 0.9 V @ 0.5 ms, P < 0.05), respectively. Conclusions IC can be recorded at the HB during permanent HBP in 37% of patients. HBIC is associated with significantly lower pacing thresholds compared to patients in whom HBIC was not recorded. HBIC may be a marker for superior short‐term HBP thresholds.